2010
DOI: 10.1007/s10805-010-9108-x
|View full text |Cite
|
Sign up to set email alerts
|

Research Ethics in a Business School Context: The Establishment of a Review Committee and the Primary Issues of Concern

Abstract: This paper describes the establishment of and the issues experienced by the Research Ethics Committee (REC) of a Business School within a University in Ireland. It identifies the issue of voluntarily given informed consent as a key challenge for RECs operating in a Business School context. The paper argues that whilst the typology of ethical issues in business research are similar to the wider social sciences, the fact that much research is carried out in the workplace adds to the complexity of the REC deliber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…For instance, Hunter [7] reports that approximately 15% of medical applications receive approval immediately. By contrast, Doyle, Mullins and Cunningham [12] report that a business school ethics committee approved 62% of applications immediately. Despite additional staffing and the introduction of procedural efficiencies, our results show that only 24% of applications got immediate approval at the monthly meeting during which applications are first reviewed (Table 2), rising to 34% in the same month as the committee meeting.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…For instance, Hunter [7] reports that approximately 15% of medical applications receive approval immediately. By contrast, Doyle, Mullins and Cunningham [12] report that a business school ethics committee approved 62% of applications immediately. Despite additional staffing and the introduction of procedural efficiencies, our results show that only 24% of applications got immediate approval at the monthly meeting during which applications are first reviewed (Table 2), rising to 34% in the same month as the committee meeting.…”
Section: Discussionmentioning
confidence: 96%
“…Should the committee be concerned with ensuring that the researcher has demonstrated that he/she has taken the time to thoughtfully consider all potential harm that may be caused by the research by completing the application form carefully and comprehensively or should standard answers copied from other application forms that have been approved, suffice?' It is our experience that supervisors frequently sign applications that fit into Doyle et al's [12] description, influenced we believe by time and deadlines as much as anything else. The Wits HREC (Medical) has yet to reach consensus on this conundrum when weighing up its dual accountabilities: firstly towards the university which, after all, bears the responsibilities of research conducted within it and secondly the postgraduates who entrust their intellectual growth and efficient throughput to the very same institution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With no existing audit of the real time required to carry out committee duties, the allocated hours in job descriptions are most likely significantly underestimated (Doyle et al, 2010) [1]. Finding suitable timings for committee meetings which allow a quorate of members to attend has always proved difficult for members with high contact teaching commitment, and again this has frequently led to ongoing delays in considering applications.…”
Section: Discussionmentioning
confidence: 99%
“…The process of reviewing research proposals and granting ethical approval is usually the remit of a Research Ethics Committee (REC), which has a pivotal role in the smooth running of research to ensure that it conforms to expected ethical norms and standards. Within this remit, the purpose of the REC is to ensure the protection of both researchers and their participants while also promoting ethical research practices and protecting the reputation of the academic institution within which they operate (Doyle, Mullins & Cunningham, 2010) [1].…”
Section: Introductionmentioning
confidence: 99%